Molecular characterization and expression patterns of MTP genes under heavy metal stress in mustard (Brassica juncea L.) - Liang You; Jialin Sheng; Guoxiang Jiang; Hao Chen; Yuhui Yuan; Sha Gong; Mingli Yan; Junhe Hu; Guohong Xiang; Renyan Duan; Yong Chen; Xianjun Liu (Scientific Reports, 2024)
Abstract Members of the Metal Tolerance Protein (MTP) family are critical in mediating the transport and tolerance of divalent metal cations. Despite their significance, the understanding of MTP genes in mustard (Brassica juncea) remains limited, especially regarding their response to heavy metal (HM) stress. In our study, we identified MTP gene sets in Brassica rapa (17 genes), Brassica nigra (18 genes), and B. juncea (33 genes) using the HMMER (Cation_efflux; PF01545) and BLAST analysis. For the 33 BjMTPs, a comprehensive bioinformatics analysis covering the physicochemical properties, phylogenetic relationships, conserved motifs, protein structures, collinearity, spatiotemporal RNA-seq expression, GO enrichment, and expression profiling under six HM stresses (Mn2+, Fe2+, Zn2+, Cd2+, Sb3+, and Pb2+) were carried out. According to the findings of physicochemical characteristics, phylogenetic tree, and collinearity, the allopolyploid B. juncea’s MTP genes were inherited from its progenitors, B. rapa and B. nigra, with minimal gene loss during polyploidization. Members of the BjMTP family exhibited conserved motifs, promoter elements, and expression patterns across subgroups, consistent with the seven evolutionary branches (G1, G4–G9, and G12) of the MTPs. Further, spatiotemporal expression profiling under HM stresses successfully identified specific genes and crucial cis-regulatory elements associated with the response of BjMTPs to HM stresses. These findings may contribute to the genetic improvement of B. juncea for enhanced HM tolerance, facilitating the remediation of HM-contaminated areas.